SEIZURE OF PROPERTY ACQUIRED BY CRIME WITH SPECIAL EMPHASIS ON THE IMPACT OF DECISIONS ON CONFISCATION OF PROPRIETY OF DEFENDANT’S FAMILY - Perišić, Jelena (Law - Theory and Practice, 2011)
In this article the author writes about the importance of having making a normative in the area of seizure of property acquired through crime on the efficiency of fighting organized crime and the prevention of profit from the crime that was later converted into legal. In the introduction the author deals with the kind of criminal sanctions and measures in our law and their origins. Hereafter reffered to comperative display solution procedures of confiscation of propriety, that served as a model of our new regulation in this area as well as view of international administrative regulation. Pass a new law on forfeiture of assets derived from crime in the body of the article is viewed in the light of respect for international law and the Constitution guaranteed. The following segment is the most basic caracteristics of newly established law. Emphasis is placed on the author of the now little-asked question of the impact the decision on confiscation of illegal property in the family of the defendant. In conclusion points to the feasibility and good performance of the new law, as well as the hope and need not to stop with a fight against organized crime groups and that the system of confiscation in our country in the future will improve.